Pd immobilized on amine-functionalized magnetite nanoparticles: a novel and highly active catalyst for hydrogenation and Heck reactions - Zhang, Fengwei; Jin, Jun; Zhong, Xing; Li, Shuwen; Niu, Jianrui; Li, Rong; Ma, Jiantai (Green chemistry : an international journal and green chemistry resource : GC, 2011)
A palladium-based catalyst supported on amine-functionalized magnetite nanoparticles was successfully prepared by a facile one-pot template-free method combined with a metal adsorption-reduction procedure. The catalyst was characterized by TEM, XRD, XPS, FT-IR and VSM. The catalyst afforded fast conversions for various aromatic nitro and unsaturated compounds, and with a turn-over frequency (TOF) of 83.33 h-1 under a H2 atmosphere in ethanol, even at room temperature. Furthermore, it was found that the catalyst showed a high activity for the Heck reaction, affording over a 93% yield in all the cases investigated. Interestingly, the novel catalyst could be recovered in a facile manner from the reaction mixture and recycled eight times without any significant loss in activity.